Women Participation in Conflict Management in Nigeria: A Case of a Rural Community in the Niger Delta Area - Kpae, Gbenemene; Masi, Juliana (American Journal of Social Sciences and Humanities, 2019)
The Niger Delta of Nigeria is plagued by crisis and youth criminality, most of which are committed by jobless and frustrated youths. Communal/ethnic, political, and youth violence are some of the crises and community leaders, the women are usually excluded due to the cultural biases against their involvement. This study examined women participation in conflict management in Omuku, bedeviling the region. Unfortunately, in an effort to manage and tackle these crises by the government Rivers State. The main objective of the research is to determine the extent of women participation in conflict management in Omuku community. The Radical Feminist and Socialist Feminist theories were used as the theoretical framework. A sample of 150 were drawn from a population of 283,292 using the purposive and snowball sampling techniques. Collected data were analysed using a descriptive method. The research found that women had very limited participation in conflict management. The research also found that women did not have any significant roles in the management of conflict in Omuku community.